Global drivers of avian haemosporidian infections vary across zoogeographical regions. Issue 12 (7th September 2021) - Fecchio, Alan; Clark, Nicholas J.; Bell, Jeffrey A.; Skeen, Heather R.; Lutz, Holly L.; De La Torre, Gabriel M.; Vaughan, Jefferson A.; Tkach, Vasyl V.; Schunck, Fabio; Ferreira, Francisco C.; Braga, Érika M.; Lugarini, Camile; et al.
Abstract: Aim: Macroecological analyses provide valuable insights into factors that influence how parasites are distributed across space and among hosts. Amid large uncertainties that arise when generalizing from local and regional findings, hierarchical approaches applied to global datasets are required to determine whether drivers of parasite infection patterns vary across scales. We assessed global patterns of haemosporidian infections across a broad diversity of avian host clades and zoogeographical realms to depict hotspots of prevalence and to identify possible underlying drivers. Location: Global. Time period: 1994–2019. Major taxa studied: Avian haemosporidian parasites (genera Plasmodium, Haemoproteus, Leucocytozoon and Parahaemoproteus ). Methods: We amalgamated infection data from 53, 669 individual birds representing 2, 445 species world‐wide. Spatio‐phylogenetic hierarchical Bayesian models were built to disentangle potential landscape, climatic and biotic drivers of infection probability while accounting for spatial context and avian host phylogenetic relationships. Results: Idiosyncratic responses of the three most common haemosporidian genera to climate, habitat, host relatedness and host ecological traits indicated marked variation in host infection rates from local to global scales. Notably, host ecological drivers, such as migration distance for Plasmodium and Parahaemoproteus, exhibited predominantly varying or even opposite effects on infection rates across regions, whereas climatic effects on infection rates were more consistent across realms. Moreover, infections in some low‐prevalence realms were disproportionately concentrated in a few local hotspots, suggesting that regional‐scale variation in habitat and microclimate might influence transmission, in addition to global drivers. Main conclusions: Our hierarchical global analysis supports regional‐scale findings showing the synergistic effects of landscape, climate and host ecological traits on parasite transmission for a cosmopolitan and diverse group of avian parasites. Our results underscore the need to account for such interactions, in addition to possible variation in drivers across regions, to produce the robust inference required to predict changes in infection risk under future scenarios.